PENGHILANGAN HAK POLITIK PERSPEKTIF SISTEM DEMOKRASI - Ansori Ansori (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2016)
Democracy is recognized as the meaning of government is from the people, by the people, for the people and together with the people. This is manifested among others by the existence of general election. How if there are some countries claimed that their countries applied democratic system without having general election. Did this case justified in a democratic system, such as Indonesian where the majority of people state that this country is part of the countries with democratic systems, but on the other hand, Yogyakarta as one of provinces of Indonesia did not organize the democratic election of governor and deputy governor which automatically removes political rights of citizens in Yogyakarta. Whereas in a democratic system, political right is part of the right to think, and it could not be removed from the people in any way and anyhow